Pengaruh Parameter Waktu Tahan Terhadap Cacat Warpage Dari Produk Injection Molding - Prabowo, Adhy Muhammad, Bambang Waluyo F., ST, MT (2017)
Injection molding is the plastic forming process by melting the plastic material to be injected into a mold. Technique can be formed to make any product design. nthis study, using polypropylene (pp) plastic material and injection moulding machine type hydraulic pneumatic with parameter holding time in 2 seconds, 4 seconds, 6 seconds, 8 seconds and 10 seconds. The results showed that the parameter of holding time in 2 seconds produce the defect because there is warpage about 255.72 mm². Additionally, parameter of holding time in 4 seconds produce to the defect because there is warpage about 143.26 mm². The parameter of holding time in 6 seconds, 8 seconds and 10 seconds showed good products and there are no warpage defects in the walls of the resulting product. Keywords : hold time parameter, warpage, injection molding.